Zamieranie olszy czarnej Alnus glutinosa (L.) Gaertn. wzdłuż rzeki Narewki na terenie Nadleśnictwa Białowieża - Malewski, Tadeusz; Nowakowska, Justyna; Oszako, Tomasz; Topor, Robert (Leśne Prace Badawcze, 2020)
Black Alder Alnus glutinosa (L.) Gaertn. is an important tree commonly growing in Poland. Alders are actinorhizal plants that play an important ecological role in riparian ecosystems through atmospheric nitrogen fixation, filtration and purification of waterlogged soils as well as providing a refuge for terrestrial and aquatic organisms thus helping to stabilize stream banks. Black Alder used to be considered a very pest and disease resistant species but, the situation changed in 2000, when an unprecedented decline of Alders was observed in Poland. In the Białowieża Forest District, this decline has been observed on wet meadow habitats and along rivers or watercourses. Currently, there are several hypotheses explaining Alder dieback, among them climatic changes and Phytophthora infections. In terms of climate, Black Alder requires a high atmospheric humidity during all phases of its reproductive cycle. It tolerates neither long-term summer flooding nor a significant decrease in the groundwater level. In terms of pests, oomycete pathogens of the genus Phytophthora are the most destructive plant pathogens known and many of them are present in forests and nurseries all over Europe. The aim of this study was to evaluate the health of Black Alder along the Narewka River in the Białowieża Forest District. Selected areas were monitored in 2012 and 2018, but no relationship between drought and alder health was found. A preliminary analysis of soil and water samples by real time PCR revealed the presence of two Phytophthora species: P. alni and P. cactorum . Further and more detailed research is required to elucidate the role of these pathogens in Alder dieback.